(untitled) (Research, Society and Development, 2022)
Attention Deficit Hyperactivity Disorder is conceptualized in two distinct aspects: the biomedical concept and the historical-behavioral theory. Many studies are focused on pedagogical strategies and methodologies that help in the therapy of children with ADHD and, consequently, in the improvement of learning, behavior and relationships, since studies on the disorder are closely linked to the school context, as this is where the diagnosis usually takes place as well as the follow-up of treatments and therapies. One of the methodologies used both in behavioral therapy and in the school context is the methodology of games or gamification, which, through play, aims to develop skills and competences as well as behavioral, social and intellectual aspects of children with ADHD. The present study aims to analyze the importance of games in the therapy of children with ADHD, weaving some characteristics in the therapy, conceptualizing gamification in the school context and relating both to the disorder. For this, we used a bibliographic research, of a descriptive and exploratory nature, regarding the proposed objectives. The resulting textual production comprises the results obtained by the bibliographic exploration of the theme, as well as by the relationship of importance analyzed. The author’s conclusions and impressions are in the final conclusions.